Evaluation of Permanent Deformation of Unmodified and Rubber-Reinforced SMA Asphalt Mixtures Using Dynamic Creep Test - Herda Yati Katman; Mohd Rasdan Ibrahim; Mohamed Rehan Karim; Nuha Salim Mashaan; Suhana Koting (Advances in Materials Science and Engineering)
This paper presents the evaluation of permanent deformation of rubber-reinforced SMA asphalt mixtures by using dynamic creep test. The effect of trans-polyoctenamer as a cross-linking agent in permanent deformation of rubberized mixtures was also evaluated. Dynamic creep test was conducted at different stress levels (200 kPa, 400 kPa) and temperatures (40°C, 50°C). Permanent deformation parameters such as dynamic creep curve, ultimate strain, and creep strain slope (CSS) were used to analyse the results. Finally, the creep behaviour of the specimens was estimated by the Zhou three-stage creep model. The results show that crumb rubber and trans-polyoctenamer significantly affected the parameters especially at high stress and temperatures. Consistent findings were observed for all permanent deformation parameters. Moreover, based on Zhou model, it was concluded that resistance to permanent deformation was improved by application of crumb rubber and trans-polyoctenamer.